Corporate finance and valuation - Ryan, Bob (Thomson, 2007)
Corporate Finance and Valuation offers a practical managerial perspective on the subject. The three themes of value, return and risk are developed and form a unifying thread throughout the book. Practical tools and techniques for identifying and solving financial problems in the real world are presented. For every practical finance problem, from estimating a companyÂ’s cost of capital through to the valuation of its intangible assets, Corporate Finance and Valuation places emphasis on how the job can be done using readily available tools and freely available data